A Review of Village Tourism in Nepal: Concept and Practice (Panauti Journal, 2024)
Nepal is a country of 753 local governments. Of the total, 736 local government (276 municipalities and 460 rural municipalities) excluding six metros and 11 sub metros are the full of village attributes-arts, culture, civilization, history and outstanding natural beauty. The transformation of village settlements into potential tourist destinations will be the village tourism initiatives in Nepal. The transformation is generally based on Tourism planning and the planning is based on its concepts and practices. Thus, the study has been conducted to identify the basic concepts and contemporary practices of village tourism in Nepal. From the methodological perspective it is a general qualitative review of recently published journal articles. The study found that village tourism helped to maintain community wellbeing and reduce poverty in homestay tourism destinations. Contrary to that community people particularly residing in other villages are still economically poor and vulnerable. Thereby, their economic poverty can be eradicated through the implementation of appropriate village tourism concepts such as smart village tourism, spatial village tourism and community based ecotourism. In doing so, 736 local government of Nepal must develop at least 5,400 community homestay (six to nine in each local level) tourism destinations. The priority must be given to Nepali tourists as well as Chinese and Indian tourists through different packages in all season and regions. Top-level political leaders and bureaucrats must be able to make diplomatic relation with China and India for promoting village tourism throughout the country.